Executive Committee Minutes 2016-02-11 - Academic Senate:::::::::
Agenda approved. Minutes of 1/28 approved. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. EPC Report. CFA Report. Associated Students Report. Faculty Eligible for Emeritus Status - approved for Senate consent calendar. Jump-Starting the Academic Planning, Assessment and Resources (APARC) committee. Appropriate actions responding to SETE discussion at Senate – referral to FSAC. Potential implications of strike dates for faculty governance. CSU CFP for affordable textbook/materials postponed to next meeting. Continued discussion of electronic agenda. Senate agenda approved. Good of the Order.